2017
DOI: 10.1039/c7nr03588h
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer-to-thin-film transition in supramolecular assemblies: the role of topological protection

Abstract: An innovative combination of TEM and STM sheds new insight into the growth of organic layers and reveals the importance of topology in controlling the transition from two- to three-dimensional structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
(54 reference statements)
3
13
0
Order By: Relevance
“…We estimated the TMA molecular lattice constant to be d TMA = 1.654 nm from the distance between the second nearest neighbors in the hexamer. This value is in good agreement with the experimental ,,,, and DFT , results.…”
Section: Resultssupporting
confidence: 91%
“…We estimated the TMA molecular lattice constant to be d TMA = 1.654 nm from the distance between the second nearest neighbors in the hexamer. This value is in good agreement with the experimental ,,,, and DFT , results.…”
Section: Resultssupporting
confidence: 91%
“…Room-temperature STM images of Nile Red deposited on Au(111) at a sub-ML coverage (∼0.5 ML) showed the formation of distinct molecular islands ranging from 10 to 40 nm in both as-deposited samples as well as those after thermal annealing at 120 °C (see Figure ). This is in line with studies using other organic compounds which found that a flat aromatic core promotes molecular adsorption and thus the formation of self-assembled molecular islands on surface terraces. In as-deposited samples, two different molecular packings of Nile Red molecules coexist on the gold surface: according to the appearance of these molecular assemblies, one was called the four-leaf clover packing and the other was called dense-chain packing (see Figure ). An extended statistical analysis carried out on different areas of as-deposited samples revealed that, at sub-ML coverage, both packings formed on the surface with equal probability.…”
Section: Results and Discussionsupporting
confidence: 82%
“…It should however be noted that the main molecular axes of the TCNQ molecules align closely to the main crystallographic directions of the Bi 2 Se 3 (0001) surface. A similar situation has been reported for the 2D self‐assembly of other organic molecules on low‐interacting substrates such as graphite or graphene and is sometimes indicated as van der Waals epitaxy…”
Section: Resultssupporting
confidence: 72%